Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/opx.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pupil Size on Wavefront Refraction during Orthokeratology

Abstract: Acknowledgement and DisclosureThis study has been funded by FEDER through the COMPETE Program and by the Portuguese Foundation for Science and Technology (FCT) diameter. The aim of this work was to evaluate the axial and peripheral refraction and optical quality after orthokeratology using ray tracing software for different pupil sizes.Methods: Zemax-EE was used to generate a series of 30 semi-customized model eyes.Refraction in the central 80º of the visual field was objectively calculated using three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
(16 reference statements)
2
32
1
1
Order By: Relevance
“…Chen et al 180 found that a larger pupil size during orthokeratology treatment in Chinese children was associated with slower axial eye growth than a smaller pupil, and suggested that this is due to a greater relative peripheral myopic shift. This change in peripheral refraction was confirmed with modelling by Faria-Ribeiro et al, 181 who also demonstrated that onand off-axis HOAs, particularly primary horizontal coma (Z 1 3 ) and primary spherical aberration (Z 0 4 ), also increase with greater pupil size as a result of corneal topographical changes during orthokeratology. This finding may indicate that HOAs influence the myopia control effect of orthokeratology; however, further longitudinal studies that examine the changes in on-and off-axis corneal and total ocular HOAs, pupil size and their association with eye growth before and during orthokeratology are required to provide further insights into a potential role for HOAs in the myopia control effect of orthokeratology.…”
Section: Orthokeratologysupporting
confidence: 65%
“…Chen et al 180 found that a larger pupil size during orthokeratology treatment in Chinese children was associated with slower axial eye growth than a smaller pupil, and suggested that this is due to a greater relative peripheral myopic shift. This change in peripheral refraction was confirmed with modelling by Faria-Ribeiro et al, 181 who also demonstrated that onand off-axis HOAs, particularly primary horizontal coma (Z 1 3 ) and primary spherical aberration (Z 0 4 ), also increase with greater pupil size as a result of corneal topographical changes during orthokeratology. This finding may indicate that HOAs influence the myopia control effect of orthokeratology; however, further longitudinal studies that examine the changes in on-and off-axis corneal and total ocular HOAs, pupil size and their association with eye growth before and during orthokeratology are required to provide further insights into a potential role for HOAs in the myopia control effect of orthokeratology.…”
Section: Orthokeratologysupporting
confidence: 65%
“…49,50 Chen et al 49 investigated the association between axial elongation and pupil size in 25 children treated with ortho-k and reported an association between slower axial elongation and larger pupil size (compared to the average sample mean). Faria-Ribeiro et al 50 analyzed the influence of pupil sizes from 3 to 6 mm in simulated eye models and suggested that the effectiveness of myopia control may be enhanced in eyes with larger pupils due to increased exposure to peripheral defocus. Therefore, not only the change in corneal optics (e.g., more positive spherical aberration), but the natural pupil size may also influence axial elongation and the extent of myopia control.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is that the numbers of children with different refractive errors (low and high myopia, high astigmatism) were not large enough to conduct separate analyses on the association between ocular HOA and axial elongation in different refractive error groups treated with ortho-k. As a result, all subjects were pooled together to provide a general understanding of the association between HOA and axial eye growth with ortho-k treatment. Because emmetropization is a complex, multifactorial process, other possible confounding factors such as pupil size, 49,50 parental myopia, 56 outdoor activities, 57 and living conditions 58 should also be evaluated in future studies (or controlled for with statistical modeling).…”
Section: Discussionmentioning
confidence: 99%
“…Together with peripheral defocus, higher-order aberrations have been associated with myopia control, mainly 4 th -order spherical aberration and coma [22, 23]. Faria-Ribeiro et al described that higher-order aberrations are associated with larger pupil diameters as well as the effect on myopia control, potentially as a result of a larger retinal area exposed to the peripheral myopic defocus [24]. Many studies have shown that higher-order aberrations increase significantly after OrthoK treatment, even in successful fittings [23, 25].…”
Section: Introductionmentioning
confidence: 99%